Time performance and CoP displacement of hemiplegic subjects in a virtual reality game task: short and long-term effects of a training protocol - Danilo de Oliveira Silva; Fábio Mícolis de Azevedo; Ronaldo Valdir Briani; Carolina Silva Flóride; Carlos Eduardo de Albuquerque; Fernando Amâncio Aragão (Universidade de São Paulo, 2015)
ABSTRACT Video games with virtual interaction have been successfully used in physical therapy programs, although there is a lack of knowledge regarding evidence involving clinical results. This study aimed to evaluate learning and some parameters of the center of pressure (COP) displacement of a Nintendo Wii Fit task in hemiplegic and healthy subjects immediately after a rehabilitation training program and after a 3-month washout period. Twenty subjects being 10 hemiplegic and 10 healthy performed three assessments over different periods; Pre, Post and 3-months after rehabilitation training. Participants were positioned on the Wii Balance Board(r). The game task performed (Ski Slalom(r) game) involved mediolateral movements. During the task's execution, the Wii Balance Board(r) was placed on a force plate (AMTI OR-6, USA). As such, COP data displacement could be collected during the game. After the training, the hemiplegic subjects showed no change in COP sway pattern and this condition persisted after three months. However, both groups improved their time performance to finish the task after training and maintained the improvement in performance after 3-months. COP displacement of hemiplegic subjects did not change after training, healthy subjects were able to reduce their mediolateral and anteroposterior COP displacement.